Inventario dendrológico del ecosistema de bosque Jacarón, cantón Colta, provincia de Chimborazo, Ecuador - Burbano, Alfonso (2014)
Is a work that seeks knowledge, conservation and management of one of the last remnants of indigenous forest paramo Ecuadorian Andes. The objective for this research were perform inventory dendrological Jacarón ecosystem of the San Antonio Association Pollongo parish Juan de Velasco, Colt Canton province of Chimborazo, determining taxonomic and soil characteristics of forest resources, assessing potential allowing knowledge of the use and utilization of existing forest resources, developing a manual dendrological species found in this area by facilitating the socialization of this knowledge to stakeholders. For this identification some bibliographic sources and turned the key to this proposed ROMAHN , C applied , although in the case of high Andean native species was necessary to go to the memory of the living monuments of the area who know these trees by their vernacular names allowing identification ; universe or population consisted of all woody plants that exist in the natural forest is 106 ha, located in three altitudinal levels , because the stand is located on a gentle slope , the study plots settled each 200 meters high , hence the division of plots by giving three floors transceiver where the same treatment was performed. Each plot was 20m wide by 50m long. In the forest 34 native tree species were identified at the level of family, genus and species abundance in determining preliminary studies of phenology and use and use of species as is done in association Pollongo, information revealed in the prepared manual. The most abundant tree plant found in all altitudinal levels, are the Tarqui ( Hedyosmun scabrum, DON ) , then Arrayan Female( Eugenia halli, L), Quinual (Polylepis reticulate,Hier), Pumamaqui Female (Oreopanax sp) and Romerillo (Podocarpus oleifolius,HBK). With these results it is concluded besides the best shaped species. Conservation, protection and management of these arboreal specimens should establish a forest of native species seedlings in height, this stand becoming a tourist attraction and maintenance of ecological identity paramo Andean cloud forest.